Xuebijing injection in the treatment of COVID-19: An update on clinical studies, potentially active metabolites and mechanisms - Zhang, Ziyan; Li, Xinyu; Zhou, Jiping; Li, Yupeng (Frontiers in Pharmacology, 2026)
IntroductionCoronavirus disease 2019 (COVID-19) is an epidemic respiratory disease caused due to the infection of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). In China, the National Health Commission of China announced that patients with COVID-19 who were treated with traditional Chinese medicines (TCMs) combined with antiviral drugs effectively alleviated their symptoms and recovered. Among these TCMs, Xuebijing (XBJ) injection plays an important role in the treatment of patients with COVID-19. However, this was a puzzle that what will be the clinical efficacy and safety of XBJ injection for COVID-19 treatment, and what are the potential mechanisms behind XBJ injection?MethodsTo search for articles on “Xuebijing injection in the treatment of COVID-19” in PubMed, use the following query: (Xuebijing injection OR Xuebijing) AND (COVID-19 OR SARS-CoV-2 OR severe pneumonia). We added filters for “Clinical Trial,” “Randomized Controlled Trial,” or “Review” to focus on specific study types, and limit the search to recent years (2010–2025) and English-language articles for more targeted results.ResultsXBJ injection in combination with regular therapy has been shown to improve overall efficacy, reduce 28-day mortality, improve lung CT recovery and reduce pro-inflammatory markers in patients with COVID-19. The high affinity for angiotensin converting enzyme 2, inhibition of neutrophil extracellular trap release and prevention of cell death and inflammation may be the main molecular mechanisms of XBJ injection in the treatment of COVID-19.ConclusionThis review synthesizes the current evidence on the clinical efficacy and safety of XBJ injection in the treatment of COVID-19. Our analysis indicates that XBJ injection, when used in combination with standard therapy, significantly improves overall efficacy, reduces 28-day mortality, enhances lung CT recovery, and decreases pro-inflammatory markers such as C-reactive protein (CRP) and interleukin-6 (IL-6). These findings suggest that Xuebijing injection is a promising adjunctive treatment for COVID-19, particularly in severe cases, although it must be confirmed through rigorous pharmacological and clinical studies.